2021
DOI: 10.1088/1742-6596/1811/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting tourist visits using data decomposition technique and learning optimization of artificial neural network

Abstract: Estimates of tourist visits is very important to determining policy and decision making. This study proposed a new method for forecasting tourist visits. A case study was conducted at a tourist spot in Sumenep, Indonesia. The model proposed is data decomposition and optimization of learning against tourist visits data. Data decomposed use the Ensemble Empirical Mode Decomposition (EEMD) method, then data learning use the Feedforward Neural Network (FNN) which was optimized using the Polak-Ribiere Conjugate Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…These are referred to as inflows and outflows, respectively. Other data presented in a study carried out by Herawati (2021) and Mensah (2021) revealed that the rise in the number of people travelling internationally has a substantial impact on the rise in the amount of money spent by consumers…”
Section: Discussionmentioning
confidence: 99%
“…These are referred to as inflows and outflows, respectively. Other data presented in a study carried out by Herawati (2021) and Mensah (2021) revealed that the rise in the number of people travelling internationally has a substantial impact on the rise in the amount of money spent by consumers…”
Section: Discussionmentioning
confidence: 99%
“…However, EMD sometimes produces mixed modes that do not match the data pattern. To overcome its weakness, Ensemble Empirical Mode Decomposition (EEMD) with the addition of white noise is used in forecasting [8]. The research integrates EEMD with an optimized artificial neural network using a genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%